2004
DOI: 10.1128/jcm.42.1.239-241.2004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Roche COBAS Amplicor Assay for Detection of Chlamydia trachomatis in Rectal and Pharyngeal Specimens by an omp1 PCR Assay

Abstract: Screening guidelines for men who have sex with men (MSM) recommend testing of extragenital sites (pharyngeal and rectal) for gonorrhoea and chlamydia. Testing of specimens from these sites is not validated by most commercial nucleic amplification tests, such as the COBAS Amplicor assay. To investigate the utility of the COBAS Amplicor assay for detection of Chlamydia trachomatis in extragenital specimens, this study developed and evaluated confirmatory tests using the omp1 gene as an alternative target for amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The high failure rate may be due to a lower sensitivity of the omp1 nested PCR because only a single-copy of the gene target, omp1, is present. In contrast, the COBAS AMPLICOR assay exhibited a higher sensitivity for targeting cryptic plasmid that is present as approximately 10 copies (Lister et al, 2004a;Mahony et al, 1993). Other studies also reported that positive genital samples identified using the COBAS or ligase chain reaction (LCR) assay could not be amplified by omp1 PCR (Pedersen et al, 2000;Vincelette et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The high failure rate may be due to a lower sensitivity of the omp1 nested PCR because only a single-copy of the gene target, omp1, is present. In contrast, the COBAS AMPLICOR assay exhibited a higher sensitivity for targeting cryptic plasmid that is present as approximately 10 copies (Lister et al, 2004a;Mahony et al, 1993). Other studies also reported that positive genital samples identified using the COBAS or ligase chain reaction (LCR) assay could not be amplified by omp1 PCR (Pedersen et al, 2000;Vincelette et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction and omp1-specific PCR were performed as described previously (20,21). Three omp1-specific PCRs were used: PCR VD1-4 with primers P1 and OMP2 to amplify a region of the gene containing all four variable domains (17), nested PCR VD1/2 with primers P1 and CT6 (5) to amplify a region containing VD1 and VD2, and nested PCR VD3/4 with primers CT6 (sense) and OMP2 to amplify a region containing VD3 and VD4.…”
Section: Methodsmentioning
confidence: 99%
“…These approaches are, in particular, important for detection from the rectum and oropharynx, which is crucial particularly in population groups of men who have sex with men (20) or with history of oral and/or anal sex. Currently, extragenital specimens are not licensed for use by the FDA; however, several studies have conducted an evaluation and shown appropriate sensitivity with these types of samples using the available commercial NAATs (21)(22)(23)(24)(25)(26)(27)(28). Nevertheless, most studies evaluating the sensitivity and specificity of the gonococcal and chlamydial NAATs utilize clinical samples whereby the gold standard for confirmation of N. gonorrhoeae is a consensus NAAT gold standard (22).…”
mentioning
confidence: 99%